Study of Biomass and Carbon Stocks of Sesbania grandiflora - Roziyanty, Rosli (2016)
Ratification of Malaysia into Kyoto Protocol could help the country to minimize the greenhouse gasses (GHG) emissions through a mechanism called Clean Development Mechanism (CDM). Carbon dioxide (CO2) globally cause problem as it is the main contributor to greenhouse gases. Therefore, there are some implementations that are implemented in order to reduce the greenhouse gases emission, such as, conserving and preserving carbon sink areas. This study investigates the biomass and carbon stocks contained in Sesbania grandiflora, an indigenous tree in Malaysia that helps in nitrogen fixation. It is also a fast growing species which help to emit carbon and one of the potential renewable energy sources. Destructive method was used in this study. The fresh mass and dry mass were weighed according to each component before the samples were grinded and sieved to become powder form. The result in this study shows the total above ground biomass of the tree is 34.93kg. The factor might be the moisture content of the tree, density and the percentage of the bark. Next, the carbon content of this tree is higher in the fruit which the average is 33.56% compared to the other components as it has high content of protein.